AgriLAC’s Guatemala Baseline datasets: Farmer and village level surveys - Reyes Padilla, Byron Alejandro; Lopera Villamarin, Diana Carolina; Quintero Cano, Diana Katherine; Ordoñez Dueñas, Juan Camilo (2025)
This dataset compiles socioeconomic, productive, and community-level information from basic grain producers in the eastern and western regions of Guatemala. It is used to characterize their initial conditions, identify productive and social patterns, and enable territorial comparisons, generating evidence to inform interventions aimed at strengthening the sustainability of basic grain systems. The data correspond to the baseline of an impact evaluation designed under a Difference-in-Differences (DiD) approach, which will allow the analysis of changes over time between treatment and control groups. This baseline, collected in 2023 with reference to the 2022 agricultural cycle, serves as the starting point for measuring the effects of the intervention in future follow-up rounds (2026–2027 and 2029–2030).